Ponatinib Activates an Inflammatory Response in Endothelial Cells via ERK5 SUMOylation - Paez-Mayorga, Jesus; Chen, Andrew L.; Kotla, Sivareddy; Tao, Yunting; Abe, Rei J.; He, Emma D.; Danysh, Brian P.; Hofmann, Marie-Claude C.; Le, Nhat-Tu (Frontiers in Cardiovascular Medicine, 2018)
Ponatinib is a multi-targeted third generation tyrosine kinase inhibitor (TKI) used in the treatment of chronic myeloid leukemia (CML) patients harboring the Abelson (Abl)-breakpoint cluster region (Bcr) T315I mutation. In spite of having superb clinical efficacy, ponatinib triggers severe vascular adverse events (VAEs) that significantly limit its therapeutic potential. On vascular endothelial cells (ECs), ponatinib promotes EC dysfunction and apoptosis, and inhibits angiogenesis. Furthermore, ponatinib-mediated anti-angiogenic effect has been suggested to play a partial role in systemic and pulmonary hypertension via inhibition of vascular endothelial growth factor receptor 2 (VEGFR2). Even though ponatinib-associated VAEs are well documented, their etiology remains largely unknown, making it difficult to efficiently counteract treatment-related adversities. Therefore, a better understanding of the mechanisms by which ponatinib mediates VAEs is critical. In cultured human aortic ECs (HAECs) treated with ponatinib, we found an increase in nuclear factor NF-kB/p65 phosphorylation and NF-kB activity, inflammatory gene expression, cell permeability, and cell apoptosis. Mechanistically, ponatinib abolished extracellular signal-regulated kinase 5 (ERK5) transcriptional activity even under activation by its upstream kinase mitogen-activated protein kinase kinase 5α (CA-MEK5α). Ponatinib also diminished expression of ERK5 responsive genes such as Krüppel-like Factor 2/4 (klf2/4) and eNOS. Because ERK5 SUMOylation counteracts its transcriptional activity, we examined the effect of ponatinib on ERK5 SUMOylation, and found that ERK5 SUMOylation is increased by ponatinib. We also found that ponatibib-mediated increased inflammatory gene expression and decreased anti-inflammatory gene expression were reversed when ERK5 SUMOylation was inhibited endogenously or exogenously. Overall, we propose a novel mechanism by which ponatinib up-regulates endothelial ERK5 SUMOylation and shifts ECs to an inflammatory phenotype, disrupting vascular homeostasis.